DETERMINAN KUALITAS HASIL PEMERIKSAAN PAJAK MELALUI PENERAPAN NILAI-NILAI ETIK KEMENTERIAN KEUANGAN - Ardi Susilo, Irawan; Parulian Ompusunggu, Arles; Djaddang, Syahril (SEKOLAH PASCASARJANA PRESS, 2018)
This research aims to examine and analyze the influence of tax auditor's competence and motivation toward tax audit quality, through the implementation of the